Effect of alveolar ridge preservation on clinical attachment level at adjacent teeth: A randomized clinical trial. (26th August 2021) - Khouly, Ismael; Strauss, Franz J.; Jung, Ronald E.; Froum, Stuart J.
Abstract: Purpose: To test whether or not alveolar ridge preservation (ARP) changes the clinical attachment level (CAL) at adjacent teeth of extraction sockets after 6 months. Material and methods: Seventeen patients requiring bilateral tooth extractions of the upper molars were recruited. After tooth extraction, the sockets were randomly allocated to two groups applying a split‐mouth design: (1) ARP using deproteinized bovine bone mineral containing 10% collagen (DBBM‐C) covered by a collagen membrane and (2) spontaneous healing (control). CAL, probing pocket depth (PD), bleeding on probing (BOP), gingival recession (REC), and bone levels were evaluated at the adjacent teeth of the extraction sockets at baseline and after 6 months of follow‐up. Results: A total of 14 patients were available for reexamination. From baseline to 6 months of follow‐up mean CAL changes of all six sites at adjacent teeth of the extraction sockets amounted to −0.23 ± 0.65 mm (gain) in ARP group and 0.05 ± 0.86 mm (loss) in the control group with significant differences in favor of ARP ( p  = 0.04). The CAL gain was significantly more favorable at mesiopalatal sites ( p  = 0.01). Consistently, the mean reduction of PD of all six sites amounted to −0.68 ± 0.84 mm in ARP and −0.34 ± 0.74 mm in the control group (intergroup p  = 0.02). The PD reduction was significant ( p  = 0.001) at the mesiopalatal sites in ARP. BOP, REC, and bone levels showed no significant differences between the groups (intergroup p  > 0.05). Conclusion: Although ARP with DBBM‐C revealed a trend toward CAL gain and PD reduction at adjacent teeth of extraction sites, these adjunctive benefits seem to be clinically negligible.